2020
DOI: 10.1080/13467581.2020.1782916
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of spatial anticrime in open communities in China

Abstract: In 2016, the Chinese government raised community opening policy for the first time. In order to study the effects of spatial anticrime in open communities, five quantifiable evaluation indexes are selected, which are "flow density, police deployment distance, spatial visibility, anti-capture ability and spatial connectivity". They are applied to the quantitative analysis of the spatial anticrime performance of two different building layouts in open community in China. The spatial anticrime analysis model from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Secondly, the correlation analysis results indicated that there was a relationship between the OSVD and all spatial attributes of the OCE, which corresponded to the findings of Kweon Jihoon, Ju Mi-Ok, and Lee Chang-Hun [95][96][97][98][99]. Specifically, teacher-student conflict, verbal bullying, and physical conflict were all found to be correlated with In, Con, and VC M (for KD1, In: p < 0.05, Con: p < 0.05, VC M : p < 0.05. for KD2, In: p < 0.01, Con: p < 0.01, VC M : p < 0.01. for KD3, In: p < 0.01, Con: p < 0.05, VC M : p < 0.05.…”
Section: Discussionsupporting
confidence: 73%
“…Secondly, the correlation analysis results indicated that there was a relationship between the OSVD and all spatial attributes of the OCE, which corresponded to the findings of Kweon Jihoon, Ju Mi-Ok, and Lee Chang-Hun [95][96][97][98][99]. Specifically, teacher-student conflict, verbal bullying, and physical conflict were all found to be correlated with In, Con, and VC M (for KD1, In: p < 0.05, Con: p < 0.05, VC M : p < 0.05. for KD2, In: p < 0.01, Con: p < 0.01, VC M : p < 0.01. for KD3, In: p < 0.01, Con: p < 0.05, VC M : p < 0.05.…”
Section: Discussionsupporting
confidence: 73%
“…To solve this problem, the urban planning policy in which an "open block" is used was put forward for the first time by the State Council of the People's Republic of China in 2016 [9]. The policy pointed out that the idea of "narrow streets and a dense network" should be gradually promoted.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…As a result, Equations (9)(10)(11)(12)(13)(14)(15)(16)(17)(18) show that two interrelated mathematical models are contained in the established bi-level multi-objective programming model. The first part addresses the optimization of the micro-circulation road network in the open block area, which involves the upper-level programming model, and the second part assigns traffic demand, which involves the lower-level programming model.…”
Section: Modelingmentioning
confidence: 99%